Discapacidad en la Facultad de Ciencias de La Salud y del ser Humano en la Universidad Estatal de Bolívar, en el cantón Guaranda período agosto 2018- febrero 2019 - Vaca Morocho, Johanna Gabriela (2019)
Disability requires a deep, multidisciplinary and reflective approach from the university chair, the workplaces and health. It must be internalized that the disability isn‟t a problem to be solved but a social responsibility to be worked from the different social spheres. The rights need to be made visible from the daily practices in order to adopt permanent measures that lead to an effective and real inclusion. The present investigation work has the purpose of analyzing the existing situation of the students with disabilities in the Universidad Estatal de Bolívar, specifically in the Faculty of Health Sciences and of the Human Being, in order to know your situation in the different dimensions like: university coexistence, university welfare, accessibility and academy through a semi-structured interview in depth the same one that will be processed in the software ATLAS TI a fundamental tool for the qualitative information analysis that allows us to know the information in hierarchies the same one that will help us to have a clearer vision of the situation in the inclusion of the students with disability. The same one that the intention to promote the inclusion in all its dimensions to adapt new teaching-learning methods according to the necessities of the students, through the training and awareness to the university community. The proposal aims to promote a culture of inclusion due to the formation of support networks among authorities, teachers, students and administrative staff.